Influence of in situ‐generated silica nanoparticles on EPDM morphology, thermal, thermomechanical, and mechanical properties. Issue 5 (3rd April 2014) - Mokhothu, T.H.; Luyt, A.S.; Morselli, D.; Bondioli, F.; Messori, M.
<x xml:space="preserve">Abstract</x> Silica nanoparticles were synthesized by means of a sol–gel method and generated in ethylene propylene diene monomer rubber (EPDM) by in situ synthesis. The properties were determined using scanning electron microscopy, attenuated total reflectance Fourier‐transform infrared spectroscopy, thermogravimetric analysis, tensile testing, dynamic mechanical analysis, swelling tests, and gel content determination. The silica particles were homogenously dispersed in the EPDM matrix, with the presence of agglomerates, especially for high silica contents. The swelling experiments showed a decrease in the crosslinking density of the vulcanized rubber due to the presence of the silica nanoparticles. The mechanical properties, however, were significantly improved by the presence of the stiff silica nanoparticles. The effect of the amount of silica on the thermomechanical properties and thermal degradation of EPDM was also investigated. The presence of silica showed an increase in the storage and loss moduli at high temperatures, probably due to the increasing filler content. The thermal degradation analysis showed that the presence of silica particles incorporated in the EPDM matrix had no significant influence on the thermal stability of the composites. POLYM. COMPOS., 36:825–833, 2015. © 2014 Society of Plastics Engineers